KEMANDIRIAN DAN KETAHANAN FINANSIAL LEMBAGA PENDIDIKAN ISLAM - Wardi, Moh.; Abdul Gafur (Pascasarjana Universitas Al-Qolam Malang, 2025)
Educational institutions teach their students about the values ​​of independence, which can shape their personality in being independent, so that it is in accordance with one of the goals of Indonesian education, namely to become independent people. And another thing is when educational institutions teach how to maintain financial resilience in educational institutions. This research aims to describe the implementation of financial independence and resilience at LPI Darul Hikam Tampojung Tenggina. The method in this research uses qualitative research methods using a descriptive approach. It also involves data collection procedures by means of interviews, observation and documentation. The results of the research can be seen from various levels of independence and financial resilience as proven by opening business units. On the other hand, there is also an evaluation related to independence and resilience.